Death of Marilyn Monroe (Module II, 2013)
USA. California, Brentwood. Clip shows ambulance arriving at house and Marilyn's body being removed. Footage includes people walking in and out of the house, reporters looking in through a window at a rumpled bed and a man wiring the window. Marilyn's covered body is wheeled out on a trolley into the ambulance.